Gagasan Simone Weil untuk Merdeka Belajar - Yohanes Deodatus (Media: Jurnal Filsafat dan Teologi, 2022)
"Merdeka Belajar" as a vision for education in Indonesia has been implemented. In February 2022, Kemendikbud launched "Kurikulum Merdeka". In addition to the objectives and practical matters, a deeper explanation of this vision is needed. Simone Weil's ideas helped find the "soul" of "Merdeka Belajar". Education in Indonesia is currently undergoing a process of decreation through what Weil calls attention, a form of self-emptying so that education can be released from the shackles of formality and the desire for artificial success today. Although humans are seen as tending to choose the easy way, Weil always encourages humans to look at what is good. One of the educational methods proposed by Weil and the vision of "Merdeka Belajar" is work or projects. Through this method and the virtue of teachers being humbler, students will be increasingly able to think independently and live their lives well into the future.